Antibacterial activity of Mentha piperita L. (peppermint) from leaf extracts – a medicinal plant - G. BUPESH; C. AMUTHA; S. NANDAGOPAL; A. GANESHKUMAR; P. SURESHKUMAR; K. SARAVANA MURALI (Acta Agriculturae Slovenica)
In the present study, we evaluated the antibacterial activity in the leaf extracts of Mentha piperita L. against pathogenic bacteria like Bacillus subtilis, Pseudomonas aureus, Pseudomonas aerogenosa, Serratia marcesens and Streptococcus aureus. The aqueous as well as organic extracts of the leaves were found to posses strong antibacterial activity against a range of pathogenic bacteria as revealed by in vitro agar well diffusion method. The ethyl acetate leaf extract of Mentha piperita showed pronounced inhibition than chloroform, petroleum ether and water, leaf extracts being more on Bacillus subtilis, Pseudomonas aerogenosa than Streptococcus aureus, Pseudomonas aureus and Serratia marcesens.